Development of an Ontology of Bulgarian Dance Folklore - Kazashka, Tsvetomira; Madanska, Sebiha; Tabakova-Komsalova, Veneta; Djeneva, Daniela; Nedelchev, Iliya (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2024)
This article introduces an ontology of a Bulgarian Dance Folklore. There are a lot of specific performances (popular in Bulgaria as ‘horá ’), but our experimental focus is on some Professor Dzhenev’s works. An ontology classifying traditional dances according to several characteristics will be considered.